Productivity Growth in Different Firm Sizes in the Malaysian Manufacturing Sector: An Empirical Investigation - Sangho Kim; Donghyun Park; Jong-Ho Park (Asian Development Bank (ADB), 2009)
Based on Cuesta (2000), this paper develops a stochastic frontier production model that allows for different groups of firms to have different patterns of technical efficiency over time. The authors apply the model to the Malaysian manufacturing sector to decompose total factor productivity growth into technical efficiency change and technical progress for different firm sizes - e.g., large and small - in seven industries during 2000–2004. The empirical results indicate that technical efficiency has worsened across all industries and firm sizes. In contrast, evidence of substantial technical progress was found in all industries. In fact, technical progress has been larger than technical efficiency deterioration in most industries and firm sizes, leading to total factor productivity growth. The analysis identifies the industries and firm sizes that lag the most in productivity, and thus have the greatest scope for policies that facilitate productivity growth.
hdl:11540/1835
Keywords: O53; 330; Capital mobility; financial crises; investment-saving gap; Asia; Industrieproduktion; Betriebsgröße; Produktivität; Industrie; Malaysia